Gestión de riesgos provocados por las altas temperaturas (estrés térmico) en los trabajadores del área de cocción de pescado y sala de compresión de amoníaco de la empresa PESPESCA s.a: implementación de un sistema de refrigeración - Reino Tene, Luis Toribio (2016)
This paper describes the study of thermal-physical conditions under which tuna cooking-area and ammonia compression area employees work at the Pespesca Company S.A. in Montecristi city and its impact on stress produced by heat. The purpose of this research was to demonstrate the extreme heat causes ricks for health, and on this base it is proposed the implementation of air conditioning systems for a comfortable working environment. Data were obtained using the thermal environments measurer and the evaluation of the heat level affecting workers using the WBGT method. Also some surveys to surveys to support the environments under study are harmful were conducted. The technical measurement used for the transmission means of the cooking area, was the implementation of wind extractors and in the compression area was the implementation of a refrigeration system detailing the equipment, resources and test in the system. In the fish-cooking area heat was reduced by using wind extractors which decreased the WBGT from 31.4°C to 26.2°C. In the ammoniac compression area, the WBGT index was also reduced from 29.3°C to 22°C. The technical management carried out in the incidence area had a very positive effect on health, since it was demonstrated that the application of the proposed methods lowered the WBGT index and therefore the rick level.